Gandrung Sewu Festivals: The Transition from Ritual Dance to Tourism Dance in Banyuwangi Indonesia - Suharti, Mamik; Sari, Cahyani Tunggal (Journal of Education Culture and Society, 2023)
Aim. Ritual ceremonies in East Java, Indonesia are mostly accompanied by dances. The existence of the seblang dance in Banyuwangi, East Java, provides an attraction for local residents and tourists. With more and more people being interested in seeing rituals because of the dance, an idea arose to bring the dance to be the main source of attracting tourists by removing the ritual element and providing tourism packaging for the seblang dance which was then brought into the realm of tourism in the form of gandrung sewu. Method. This research is qualitative in nature, in which the required data can be in the form of written statements, whether contained in archives, books or documents with a focus on dance performances, charms in them, the possibility of therapeutic elements, and their relation to tourism development. The written data that was successfully collected was then confirmed with field data and information from relevant experts and experts. Results. The Gandrung Sewu Festival is a form of imitation of the Seblang dance with changes such as: a colossal form of variation, the audience does not need to pay to see it, has an economic and social impact on the surrounding environment, does not have a magical element but is more of a show, and is an imitation of the seblang sacred dance. Conclusion. The change in form and meaning of the Gandrung dance, which was originally a performance in a sacred ceremony, has become a tourism dance that meets the criteria for tourism art.